Eco Literacy in Z Generation Regarding Waste Management as a Critical Dimension of Sustainable Urban Green Space - Purwono, Purwono; Setiyaningrum, Ika Feni; Silviani, Wahyu Dian; Fatmawati, Puput Yosi; Adji, Diva Permata (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Green spaces will only be adequately maintained with the active support of residents. Eco-literacy in the Z generation is essential in encouraging the behavior of those who care about the environment. The research was conducted using quantitative methods by sending questionnaires to Z-generation respondents. The questionnaire uses Likert scale including indicators scientific integration, program sustainability, internet literacy, the importance of waste management, concerns about waste, and volunteers. The majority of Z generation agrees that scientific integration educates them about environmental challenges and waste management. Concerning programmed sustainability, they are neutral about waste management programmed in schools. They appreciate environmental issues and try to educate the people using the internet. They feel good waste management will affect the environment, agree that Z generation is concerned about waste, and volunteer extensively for the environment.